The effect of Malus doumeri leaf flavonoids on oxidative stress injury induced by hydrogen peroxide (H2O2) in human embryonic kidney 293 T cells - Yanyan Li; Yunyi Li; Zhie Fang; Dan Huang; Yalin Yang; Dijia Zhao; Mingchun Hang; Junda Wang (BMC, 2020)
Abstract Background In this study, Malus doumeri leaf flavonoids (MDLF) were used as the research object to observe their in vitro antioxidant stress ability. Hydrogen peroxide (H2O2) was used to induce oxidative stress in 293 T cells. Methods MTT, flow cytometry, and qPCR were used to verify the effect of MDLF. Results In vitro cell experiments showed that at a concentration of 0-160 μg/mL, MDLF did not affect the normal proliferation of human embryonic kidney 293 T cells (HEK 293 T cells), and MDLF had no cytotoxic effect in this concentration range. It was found that MDLF could maintain the survival of HEK 293 T cells (82.6%) at a high concentration (160 μg/mL). Morphological observation also found that MDLF can inhibit the cell structure imperfection caused by H2O2. It was also observed that MDLF could significantly increase the levels of catalase (CAT), superoxide dismutase (SOD), glutathione (GSH), and glutathione peroxidase (GSH-Px) and reduce the level of malondialdehyde (MDA). The results of quantitative polymerase chain reaction (qPCR) showed that MDLF could significantly up-regulate the mRNA expression levels of CAT, SOD, GSH, GSH-Px, B-cell lymphoma-2 (Bcl-2) and downregulate the expression levels of B-cell lymphoma-2 associated x protein (Bax), tumor necrosis factor-alpha (TNF-α), and nuclear factor kappa-B (NF-κB) in oxidative stress-injured cells. The HPLC analysis showed that MDLF contained hyperin, isoquercetin, quercitrin, hesperidin, myricetin, baicalin and quercetin. Conclusion From the experimental results, it was observed that MDLF has a strong anti-oxidation ability in vitro, and it can interfere with the oxidative stress damage caused by H2O2 in 293 T cells. Therefore, MDLF is a type of natural substance with good anti-oxidant effect, and it has the potential to interfere with many diseases.